Temporal changes in volatile profiles of Varroa destructor-infested brood may trigger hygienic behavior in Apis mellifera - Liendo, María Clara; Muntaabski, Irina; Russo, Romina Maria; Lanzavecchia, Silvia Beatriz; Segura, Diego Fernando; Palacio, María Alejandra; Cladera, Jorge Luis; Fernández, Patricia Carina; Scannapieco, Alejandra Carla (Wiley, 2022)
Varroa destructor Anderson & Trueman (Acari: Varroidae) is one of the major contributors to the significant losses of western honey bee, Apis mellifera L. (Hymenoptera: Apidae), colonies worldwide. Hygienic behavior, in which individual workers detect, uncap, and remove unhealthy brood, is a type of social immunity that reduces pathogen and parasite loads in the colony. Previous evidence suggests that hygienic worker bees identify diseased brood through olfactory cues. The aims of the present work were (1) to study the hygienic behavior of worker bees toward V. destructor-infested cells at different stages of brood development, (2) to explore changes in brood volatile profiles associated with the progression of mite infestation, and (3) to analyze the role of specific volatile compounds in triggering the hygienic behavior. Results showed that the removal rate of infested brood changed along its development and the progression of mite reproduction. Two compounds, ethyl hexanoate and α-pinene, were present in volatile collections from mite-infested pupae but absent from uninfested pupae. Field bioassays showed that these volatiles are relevant to elicit the hygienic behavior. A third compound, β-ocimene, was present in infested and uninfested brood but its abundance pattern varied according to the infestation status throughout brood development. Specifically, for uninfested brood, the abundance of β-ocimene showed a reduction in black-eyed pupae, whereas for infested brood, its abundance decreased drastically in light-pink-eyed pupae and remained constant in black-eyed pupae. Our results revealed that olfactory signals associated with V. destructor infestation change as the reproductive cycle of V. destructor progresses inside the cell. These changes can be mimicked to some extent by adding specific volatile compounds to the cell to induce hygienic removal. These findings shed light on the chemical basis of hygienic behavior against V. destructor and could facilitate the development of improved hygienic selection tools to breed mite-resistant honey bee colonies.